2009
DOI: 10.1097/scs.0b013e3181a14c79
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Mandibular Canal and the Topography of Its Neurovascular Structures

Abstract: The major complication in dental implant surgery is loss of sensation due to damage to the inferior alveolar nerve resulting from poor characterization of the location of the mandibular canal and the traveling course of the inferior alveolar nerve, artery, and vein therein. The purposes of this study were to determine the buccolingual location of the mandibular canal and to verify the topography of the inferior alveolar nerve, artery, and vein therein by three-dimensional reconstruction of these structures. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 18 publications
(9 reference statements)
7
47
0
4
Order By: Relevance
“…in the molar area, the mandibular canal was either in contact with the lingual cortex or ran very close to the lingual cortex while in the premolar area, the mental nerve usually makes a sharp turn from lingual to buccal and exits through the mental foramen. Similar courses have been recorded by several other investigators [13,[19][20][21]. The buccolingual course of the MC becomes more important in cases of deficiency of the vertical dimension of the alveolar ridge.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…in the molar area, the mandibular canal was either in contact with the lingual cortex or ran very close to the lingual cortex while in the premolar area, the mental nerve usually makes a sharp turn from lingual to buccal and exits through the mental foramen. Similar courses have been recorded by several other investigators [13,[19][20][21]. The buccolingual course of the MC becomes more important in cases of deficiency of the vertical dimension of the alveolar ridge.…”
Section: Discussionsupporting
confidence: 67%
“…The buccolingual course of the MC becomes more important in cases of deficiency of the vertical dimension of the alveolar ridge. Kim et al, (2009) [21] suggested that implants may be placed buccal to the mandibular canal with minor adjustment of angulation when itscourse runs close to the lingual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the alveolar nevre is largely due to insufficient information about the location of the mandibular canal and it is one of the most frequent complications. Such damage can also occur in the absence of knowledge about the traveling courses of the IAN, artery, and vein within the mandibular canal (Kim et al, 2009). Neuropathic pain associated with implant placement is rare in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of sensory changes can be evaluated using three types of measures: (i) objective electrophysiological measures of nerve conduction, (ii) sensory testing measures and (iii) patient report (Takazakura et al, 2007). The request of replacing missing teeth with dental implants is increasing, and as a result, incidence of postoperative complications is increasing concomitantly (Kim et al, 2009). When the height of bone between alveolar crest and inferior alveolar canal is insufficient, implant placement in the posterior mandible is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Constitui-se, ainda, um método não invasivo, rápido, fidedigno e de grande valor diagnóstico (Rodrigues e Vitral, 2007). Embora a osteologia mandibular já tenha sido descrita em algumas espécies, a exemplo do homem (Suazo et al, 2007;Kim et al, 2009) e do cão (Villamizar Martinez et al, 2009), a literatura é escassa quanto à osteologia craniana dos felinos, sejam estes domésticos ou provenientes de habitat selvagem (Christiansen, 2008). Sabe-se que várias afecções dentárias dos felinos podem evoluir para uma agressão ou dano ao CM, a exemplo da lesão de reabsorção, necessitando de intervenção cirúrgica (Reiter et al, 2005).…”
unclassified